2021
DOI: 10.1001/jamanetworkopen.2021.22837
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Duration With All- and Major-Cause Mortality Among Adults in Japan, China, Singapore, and Korea

Abstract: IMPORTANCE The association between long sleep duration and mortality appears stronger in EastAsian populations than in North American or European populations.OBJECTIVES To assess the sex-specific association between sleep duration and all-cause and majorcause mortality in a pooled longitudinal cohort and to stratify the association by age and body mass index. DESIGN, SETTING, AND PARTICIPANTS This cohort study of individual-level data from 9 cohortsin the Asia Cohort Consortium was performed from January 1, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 39 publications
(69 reference statements)
8
49
0
Order By: Relevance
“…In keeping with our findings, another recent large-scale study reported a 20% increased cancer mortality risk among East Asian women with a sleep duration of ≥10 vs 7 hours. 36 Few studies have evaluated the relationship between sleep duration and total cancer incidence among Asians. 11 In a 2018 metaanalysis of cohort and case-control studies conducted in the United States, Asia and Europe, Chen et al 11 reported no association between sleep duration and total cancer incidence in both men and women, which is consistent with our results in men but not women.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with our findings, another recent large-scale study reported a 20% increased cancer mortality risk among East Asian women with a sleep duration of ≥10 vs 7 hours. 36 Few studies have evaluated the relationship between sleep duration and total cancer incidence among Asians. 11 In a 2018 metaanalysis of cohort and case-control studies conducted in the United States, Asia and Europe, Chen et al 11 reported no association between sleep duration and total cancer incidence in both men and women, which is consistent with our results in men but not women.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38] However, self-reported sleep duration has important health implications, including consistent association with mortality across different populations. [39][40][41][42] Additionally, for the entire study period, we lacked other information that may have provided a more in-depth understanding of these disparities, such as quality of sleep, other sleep duration alterations, and medications that may alter sleep pattern and duration.…”
Section: Discussionmentioning
confidence: 99%
“…People with short or long sleep are at increased risk of depression, reduced quality of life, cardiovascular disease, diabetes, and death, among other conditions. [42][43][44][45] Such a persistent gap in sleep duration may thus be a cause and exacerbator of other health disparities, and may serve as an imperfect indicator of overall disparities in health and well-being. For the national objective of achieving health equity, understood as the assurance of the condition of optimal health for all people, 46 it is thus instrumental to also strive for the elimination of socioeconomic and health conditions that prevent racial and ethnic minorities from achieving adequate sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When describing the characteristics of participants, both of total sleep duration and nocturnal sleep duration at baseline were divided into six groups: ≤5, 6, 7, 8, 9, and ≥10 h. Post-lunch napping was divided into four groups: <30, 30–90, and >90 min. The cut points for sleep durations and post-lunch napping were according to previous studies ( 15 , 32 ). Changes in sleep duration over time were evaluated from baseline to 2013 wave 2, and from baseline to 2015 wave 3.…”
Section: Methodsmentioning
confidence: 99%